Analysis of Crew Readiness for Anchoring on the KMP Trisna Dwitya - Kadek Karlina; Anak Agung Istri Sri Wahyuni; Indah Ayu Johanda Putri; Anak Agung Ngurah Ade Dwi Putra Yuda (International Journal of Science and Environment (IJSE), 2026)
The crew's readiness to anchor on the KMP Trisna Dwitya is still lacking, which has the potential to affect navigation safety. This study aims to identify the crew's readiness to anchor and identify factors that influence the implementation of anchoring maneuvers on the KMP Trisna Dwitya ship. The research method used is descriptive qualitative with primary and secondary data sources. Data collection techniques were carried out through observation, direct interviews with the captain, chief officer, second officer, helmsman, boatswain, and documentation, while data analysis used the fishbone method to regularly identify causal factors. The results show that in general the implementation of anchor on the KMP Trisna Dwitya has run well and according to procedures, starting from the selection of the anchoring site to the adequate anchoring process. Most of the navigation tools functioned well such as Radar, GPS, ECDIS, Echo Sounder, but were hampered by the windlass which was jammed and the anemometer was not working, the bridge-bow communication was less effective when using a handy talky, as well as strong currents and dense traffic in the Bali Strait which affected the maneuvering process. In conclusion, the ship's crew is ready to carry out the anchoring maneuvering process but needs to carry out routine equipment maintenance, briefing before the anchoring process, and procurement of anemometer navigation tools to reduce the risk of accidents and improve safety.